The Differential Effect of Excess Aldosterone on Skeletal Muscle Mass by Sex - Kwak, Mi Kyung; Lee, Seung-Eun; Cho, Yoon Young; Suh, Sunghwan; Kim, Beom-Jun; Song, Kee-Ho; Koh, Jung-Min; Kim, Jae Hyeon; Lee, Seung Hun (Frontiers in Endocrinology, 2019)
The effects of excess aldosterone on skeletal muscle in individuals with primary aldosteronism (PA) are unknown. To examine the effects of aldosterone on skeletal muscle mass in patients with PA, Three hundred and nine consecutive patients were enrolled. Skeletal muscle and fat mass of 62 patients with PA were compared with those of 247 controls with non-functioning adrenal incidentaloma (NFAI). Body composition parameters were measured using bioelectrical impedance analysis, and plasma aldosterone concentration (PAC) was measured using a radioimmunoassay. The PAC in all women, but not men, showed an inverse association with appendicular skeletal muscle mass (ASM) (β = -0.197, P = 0.016) and height-adjusted ASM (HA-ASM) (β = -0.207, P = 0.009). HA-ASM of women, but not men, with PA was 5.0% lower than that with NFAI (P = 0.036). The odds ratio for an association between low HA-ASM and PAC in women was 1.18 [95% confidence interval (CI), 1.01–1.39; P = 0.035], and that for an association between low HA-ASM and PA was 10.63 (95% CI, 0.83–135.50; P = 0.069). Skeletal muscle mass of women with PA was lower than that of women with NFAI, suggesting that excess aldosterone has adverse effects on skeletal muscle metabolism.